Understanding roles of Zr and W on hot/warm deformation behavior of FeCrAl alloy: Grain boundary features and dynamic precipitation of Laves phase. (January 2022) - Liu, Wenbo; Liu, Zhe; Luo, Wei; Liu, Huiqun; Wang, Qing; Zhang, Ruiqian
Abstract: The present work investigated the hot (800–1100 °C) and warm (600 °C) deformation behavior of Fe–13.5%Cr–4.7%Al–2.0%Mo–1.0%Nb (wt.%) (FeCrAl), Fe–13.5%Cr–4.7%Al–2.0%Mo–0.9%Nb–0.11%Zr (wt.%) (FeCrAl–Zr) and Fe–13.5%Cr–4.7%Al–1.4%Mo–1.0%Nb–1.32 W (wt.%) (FeCrAl–W) ferritic stainless steels using a thermal simulation machine at strain rates of 0.01–10 s −1 . Before deformation, all the samples were solution-treated at 1150 °C, 1250 °C, and 1200 °C for FeCrAl, FeCrAl–Zr, and FeCrAl–W alloys, respectively. The stress–strain curves showed dynamic softening in FeCrAl, FeCrAl–Zr, and FeCrAl–W alloys, and processing maps were also constructed. A large number of low-angle grain boundaries (LAGBs) could be created by hot (800 °C) and warm (600 °C) deformation, and Zr/W slightly increased the proportion of LAGBs in the samples deformed at 800 °C and 1100 °C. In addition, both lower deformation temperature (800 °C), higher strain rate (1 s −1 ), and Zr/W addition could significantly increase the size of the precipitate-free zone and the content of grain boundary precipitates during hot deformation, which could result in the hysteresis phenomenon of the softening behavior. These results can be expected to provide guidance for the subsequent determination of possible hot and warm processing of FeCrAl alloys. Highlights: True stress–strain curves of Fe–Cr–Al alloy exhibited dynamic softening. Amount of LAGBs can be created by hot (800 °C) and warm deformation. Zr/W addition slightly increased the peak stress during hot deformation. Zr/W addition increased the width of PFZ during hot deformation.